Application of Sorbents for Industrial Waste Water Purification. Issue 4 (23rd February 2015) - Matejkova, Martina; Soukup, Karel; Kastanek, Frantisek; Capek, Pavel; Grabowski, Jacek; Stanczyk, Krzysztof; Solcova, Olga; Kristal, Jiri
Abstract A sorption technique was tested for decontamination of post‐processing underground coal gasification (UCG) water contaminated by a variety of organic and inorganic substances. Four sorbents (two zeolites and two activated carbons) with nanoiron were chosen for laboratory and pilot sorption experiments. Four main phenol contaminants typical for UCG water served as markers for sorption efficiency. Axial dispersion was evaluated for three pilot channel positions filled with gravel, sand, and sand with stones. Both activated carbons revealed the best sorption efficiency in laboratory as well as in pilot experiments for organic and inorganic contaminants. A sandwich structure of different sorbents was suggested as the optimal design of a reactive bed suitable for tests in the experimental mine.